Community Empowerment in Handling Non-Communicable Diseases Through Self-Medication and Use of Toga in Alale Village, Central Suwawa District, Bone Bolango Regency - Hartati Hartati; Vyani Kamba; Insyira Fadliana Basri (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Self-medication is an effort in treatment that is carried out independently. Based on data from the Central Statistics Agency (BPS) for 2019 regarding health indicators for the Indonesian population, it is known that the data obtained on self-medication by Indonesian people from 2017 to 2019 for self-medication has increased from 71.46%. In Gorontalo Province, self-medication has been carried out by 76.60% of the population. Preliminary studies that have been carried out, many people in Alale Village, Suwawa Tengah District, buy drugs at the weekly market with the intention of self-medication, but there is still a lack of knowledge of proper self-medication and the use of natural plant materials as an alternative treatment. This community service aims to apply the results of research related to self-medication carried out by the community in increasing immunity during the current COVID-19 pandemic. The application is manifested in the form of CBIA (Community Based Interactive Method) in the form of counseling in the form of lectures, discussions, consultations, educational games as well as training assistance for cadres/community groups related to procedures for making traditional ingredients using plants in the surrounding environment. This is to increase knowledge and understand procedures for self-medication using conventional medicines and traditional medicines in the form of Family Medicinal Plants (TOGA) in dealing with non-communicable diseases, especially at the location of the community service implementation. Community service activities in Alale Village, Central Suwawa District, Bone Bolango Regency were carried out in 2 (two) stages, where stage I included a pretest prior to socialization, providing material and outreach about self-medication, providing drug information services, providing training on how to make simple traditional concoctions. Phase II includes monitoring of self-medication actions, mentoring and monitoring of making samples of Family Medicinal Plants (TOGA), and evaluation through posttest. The evaluation results obtained from the survey on community service activities show that the community's understanding has increased from 55.5% to 90%. This shows that community service activities have succeeded in increasing the understanding of the people of Alale Village.